The Impact of Laguna Beach Tourism on Social Change in the Community of Pao-Pao Village, Tanete Rilau District, Barru Regency, South Sulawesi - Ayu, Ayu Dwi Saputri Wahab; Amiluddin, Amiluddin; Amri, Andi; Wahid, Abdul; Mustafa, Muhammad Dalvi (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2023)
This study aims to determine the condition and management of the Laguna beach tourist destination and describe the socio-economic impact of Laguna beach tourism on the social changes of the people of Pao-Pao Village, Tanete Rilau District, Barru Regency. This research was conducted in January-February 2022. The sampling method used was the purvosive sampling method with the following criteria, informants and the entire community who were considered to know in-depth information and problems and could be trusted as valid data sources and were willing to be interviewed. The data sources used are primary data and secondary data. In Laguna beach tourism there are socio-economic impacts that affect the survival of the community which are felt by managers, traders/business actors and the local community, where the social impact on Laguna beach tourism, the community experiences changes in people's thinking patterns in responding to education and the times so that social interaction develops. over time, but it can still be monitored and overcome if it is negative and the economic impact that occurs, the community can open a business/sell-sell so as to increase their income. In improving the social welfare of the community, it can be done by developing lagoon beach tourism with the support of good facilities and infrastructure, cleanliness and safety as well as socio-economic impacts that provide social change for the community, whether it is a decent and harmonious life, even though the changes require a long period of time.